Billions of impoverished people deserve to be better served: A call to action for the service research community - Raymond P. Fisk; Laurel Anderson; David E. Bowen; Thorsten Gruber; Amy Ostrom; Lia Patricio; Javier Reynoso; Roberta Sebastiani (2016)
Purpose – The purpose of this paper is to create a movement within the service research community that aspires to help the billions of impoverished people across the world achieve better service from each other, from their communities, from corporations, from their governments, and from nongovernmental organizations. The authors believe every human being is worthy of being served properly. To achieve this purpose, understanding and learning from this huge low-income segment of society known as the base of the pyramid (BoP) is essential. There are myths about the BoP that need to be dispelled and there is a fundamental lack of service research on this important problem. Design/methodology/approach – The existence of an extensive BoP literature combined with service research priorities has called attention to drafting research agendas. Human service systems are explored historically and systems theory provides a perspective for understanding and reducing poverty. Transformative service research, service design research, and community action research are presented to illustrate three research approaches that can contribute to understanding and then better serving the needs of the neglected billions of humanity. Findings – First, the authors present a practical and meaningful call to action by making the case for the service research community to contribute to poverty alleviation with the creation of fresh ideas and research agendas. Second, the authors describe the ample opportunity for conducting service research in and with the BoP and thereby expanding service knowledge about the BoP. Third, the authors suggest a number of approaches for service researchers to join this new movement and help improve the well-being of billions of impoverished people. Social implications – Most existing service research comes from highly developed Anglo-Saxon countries and concerns the service problems of customers in affluent societies. Therefore, there is a fundamental lack of service research at the BoP. The social implications are truly global. Poverty is a global service system problem that can be reduced. Effective poverty alleviation solutions in one part of the world can be adapted to other parts of the world. Originality/value – This paper is a new and very original call to action to the service research community. First, with the exception of a few previous manuscripts calling for research on the BoP, this is the first time a collaborative effort has been made to start systematically changing this knowledge gap. Second, the service research community has never worked on a project of this magnitude. The authors hope to offer a role model to other academic communities as to how to marshal their resources to have a collective, positive impact on the well-being of the world’s impoverished.